A conceptual framework for the implementation of corporate social responsibility practices and performance - Mohd Fuzi, Nursyazwani; Habidin, Nurul Fadly; Ashaari, Azmirul; Abdullah, Mazilah; Adam, Sabrinah; Md Salleh, Nor Zafir; Yong, Sharon Yee Ong (Human Resource Management Academic Research Society, 2022)
This paper presents a conceptual framework that guides organizations through Corporate Social Responsibility (CSR) practices and CSR performance in Malaysian automotive suppliers. It provides a framework based on CSR practices dimensions (employee involvement, customer focus, environment, corporate governance, community and society, and human right) and CSR performance measurements (social performance and environmental performance). CSR practice plays a vital role in contributing to developing employees, communities, and customers to improve the CSR performance for Malaysian automotive suppliers. This’s main contribution is to link the CSR implementation practices initiatives and CSR performance measurement.